Original paperHigh-dose-rate brachytherapy delivered in two fractions as monotherapy for low-risk prostate cancer - Cendales, Ricardo; Alwers, Elizabeth; Cifuentes, Javier; Bobadilla, Ivan; Torres, Felipe; Arbelaez, Juan; Gaitan, Armando; Cortes, Helber; Acevedo, Yenny; Quintero, Paulo; Vasquez, Jaider (Journal of Contemporary Brachytherapy, 2015)
Purpose: High-dose-rate (HDR) brachytherapy has been accepted as an effective and safe method to treat prostate cancer. The aim of this study was to describe acute toxicity following HDR brachytherapy to the prostate, and to examine the association between dosimetric parameters and urinary toxicity in low-risk prostate cancer patients. Material and methods : Patients with low-risk prostate cancer were given HDR brachytherapy as monotherapy in two 12.5 Gy fractions. Planning objectives for the planning target volume (PTV) were V 100 % ≥ 90% and V 150 % ≤ 35%. Planning objectives for organs at risk were V75% ≤ 1 cc for the bladder, rectum and perineum, and V125% ≤ 1 cc for the urethra. Toxicity was assessed three months after treatment using the Common Terminology Criteria for Adverse Events. Results: Seventy-three patients were included in the analysis. Thirty-three patients (45%) reported having any type of toxicity in the three months following HDR brachytherapy. Most toxicity cases (26%) were grade 1 urinary toxicity. Mean coverage index was 0.89 and mean V 100 was 88.85. Doses administered to the urethra were associated with urinary toxicity. Patients who received more than 111.3% of the prescribed dose in 1 cc of the urethra were four times more likely to have urinary toxicity compared to patients receiving less than 111.3% (OR = 4.71, 95% CI: 1.43-15.6; p = 0.011). Conclusions : High-dose-rate brachytherapy administered as monotherapy for prostate cancer proved to be a safe alternative treatment for patients with low-risk prostate cancer. Urinary toxicity was associated with the dose administered to 1 cc and 0.1 cc of the urethra and was remarkably inferior to the reported toxicity in similar studies.